Analisis Sistem Antrian Pelayanan dan Kedatangan Pelanggan Dengan Menggunakan Qm For Windows Pada Indomaret Aek Batu - Fitria, Annisa Pribadi; Risnawati, Risnawati; Rambe, Dedi Purnama; Situmorang, Bima Muhammad; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
Queue is an activity of waiting in a line carried out by customers or goods to obtain service facilities. Queue is a Waiting Line of Customers measured by certain units that require one or more services. Queue Analysis is a form of probability analysis. Queues are often encountered in everyday life. The queuing process is a process related to the arrival of customers at a service facility, waiting in a queue if they have not been served, being served and finally leaving the facility after being served. Someone has to wait which takes time. The purpose of this observation is to find out the queuing system at Indomaret Aek Batu and to find out the optimal cashier service. The first step taken is to observe customer arrivals. The analysis process uses